Mechanical and Creep Behavior of Advanced Materials A SMD Symposium Honoring Professor K. Linga Murty - Charit, Indrajit; Zhu, Yuntian T.; Maloy, Stuart A.; Liaw, Peter K.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This collection commemorates the occasion of the honorary symposium that celebrated the 75th birthday and lifelong contributions of Professor K.L. Murty. The topics cover the present status and recent advances in research areas in which he made seminal contributions. The volume includes articles on a variety of topics such as high-temperature deformation behaviors of materials (elevated temperature creep, tensile, fatigue, superplasticity) and their micromechanistic interpretation, understanding mechanical behavior of HCP metals/alloys using crystallographic texture, radiation effects on deformation and creep of materials, mechanical behavior of nanostructured materials, fracture and fracture mechanisms, development and application of small-volume mechanical testing techniques, and general structure-property correlations.
Part 1: Mechanical Anisotropy, Crystallographic Texture and Related Phenomena -- Creep, Deformation and Fracture Studies of Materials for Various Technologies in the Nuclear Materials Research Group at NC State -- Anisotropic Biaxial Creep of Textured Nb-modified Zircaloy-4 Tubing -- Effect of Specimen Geometry, Orientation and Temperature on the Impact Toughness of Zr-2.5Nb Pressure Tube -- Microstructure, Texture and Mechanical Properties of the 14YWT Nanostructured Ferritic Alloy NFA-1 -- Irradiation Creep of Zr-Alloys -- Part 2: High Temperature Creep of Structural Materials -- Fundamentals of Creep in Aluminum Over a Very Wide Temperature Range -- Dislocation Cross-Slip Controlled Creep at High Stresses and Transitional Creep Mechanisms in Zircaloy-4 -- TerraPower HT9 Mechanical and Thermal Creep Properties -- Part 3: Advanced Materials and Processing -- Applying Conventional Creep Mechanisms to Ultrafine-Grained Materials -- On the Strain Rate Sensitive Characteristics of Nanocrystalline Aluminum Alloys -- Part 4: Materials for Nuclear Environments -- Synergistic Effects of Neutron Irradiation and Interstitial Nitrogen on Strain Aging in Ferritic Steels -- Part 5: Creep, Creep-Fatigue and Related High Temperature Mechanical Behavior -- Cyclic Deformation Behavior of Modified 9Cr-1Mo Steel at Elevated Temperatures -- Characterisation of Mechanical Properties Using Ball Indentation, Small Punch Creep and Impression Creep Methods -- Part 6: Structure-Property Relations and Fracture Behavior in Advanced Materials -- 2017 TMS Keynote Abstract: Superhard Materials: Discovery of Q-phases and Direct Conversion of Carbon into Diamond and h-BN into c-BN -- Surface Finish Effects on Fracture Behavior of Sn-4Ag-0.5Cu Solder Joints -- Mechanical and Microstructural Effects of Thermal Aging on Cast Duplex Stainless Steels by Experiment and Finite Element Method -- Digital Stress Imaging in Mesoscale Microstructure Dependent Deformation Visualized Using Nano-mechanical Raman Spectroscopy: Role ofInitial Manufacturing Originated Residual Stresses -- Fracture Behavior and Grain Boundary Sliding during High-Temperature Low-Stress Deformation of AZ31 Magnesium Alloy -- Part 7: Mechanical Behavior of Titanium and Zirconium Containing Alloys -- Creep of Zirconium and Zirconium Alloys -- Effect of Mo and Bi Additions on the Microstructure of Zr-Cr-Fe alloy After ß-quenching -- Part 8: Poster Session -- Effects of Blade Curvature on Fatigue Life of Nickel-Based Single Crystal Structures with Film-Cooling Holes -- High Temperature Tensile Properties and Related Microstructural Evolution of Grade 92 Steel -- Understanding of Microstructure and Mechanical Properties of Friction Stir Processed Al-Bearing, High-Cr Ferritic Stainless Steel.
Keywords: Materials -- Analysis; Building materials; Materials; Characterization and Analytical Technique; Structural Materials; Materials Engineering